Optical properties of Eu3+ ions in boro-tellurite glass - Tam, Ngo Van; Tuyen, Vu Phi; Do, Phan Van (Communications in Physics, 2016)
The excitation, emission spectra and and lifetime of Eu-doped borotellurite glasses (BTe) have been investigated. The sideband phonon energy and electron-phonon coupling strength (g) have been found. The intensity parameters Ωλ were calculated from the emission spectrum. These parameters were used to predict radiative properties such as transition probabilities (AR), calculated branching ratios (βR) and stimulated emission cross-sections (σλp) for 5D0→7HJHFJ transitions.